Procyanidin B2 of Cassia fistula a Potent Inhibitor of COVID19 Protease: A Molecular Dynamic Simulation Analysis - Ravi, Dr. Lokesh (Asian Journal of Pharmaceutics (AJP), 2020)
Based on molecular dynamic simulation studies and â€œSiddhaâ€ medicinal practice, this study proposes that, Cassia fistula fruit pulp consists of procyanidin B2, which is a potential protease inhibitor that can be used for the treatment of COVID19 infection. Virtual drug screening method and MD simulation were used to analyze 430 phytochemicals of 20 ethnobotanical medicinal plants suggested by Siddha medicine practitioner as antiviral sources and treats symptoms related to COVID19. MD simulation strongly suggested that procyanidin B2 exhibits strong protease inhibition potential, better than the co-crystallized reference ligand O6K. Scientific evidence states that C. fistula exhibits significant antiviral activity against human viral infections in addition to other medicinal activities. The fruit pulp of C. fistula is a readily market available product that can significantly aid in recovering the COVID19 infected patients from complications. It is proposed to the research centers and clinics that are currently treating the COVID19 patients to make an attempt to use the C. fistula fruit pulp as a hot water extract to improve the patientâ€™s response and prevent further mortalities due to the same.